E-052 Robotic digital subtraction angiography systems within the hybrid operating room. (16th November 2010) - Murayama, Y; Ishibashi, T; Ebara, M; Ikeuchi, S; Takao, H; Arakawa, H; Kato, M; Kobayashi, N; Abe, T
Abstract : Objective: The authors describe the experience of robotic digital subtraction angiography (DSA) system in the hybrid operation room (OR) Methods: A newly designed robotic DSA system (Artis zeego; Siemens AG, Erlangen, Germany) was installed in one of the hybrid OR. The system consists of a multi-axis robotic C arm and surgical OR table. In addition to conventional neuroendovascular procedures, the system was used as an intraoperative imaging tool for various neurosurgical procedures such as aneurysm clipping or spine instrumentation. Results: 501 neurosurgical procedures were successfully conducted in the hybrid OR using robotic DSA. During surgical procedures such as aneurysm clipping or arteriovenous fistula treatment, intraoperative two-dimensional/three-dimensional angiography and C arm based CT images (Dyna CT) were easily performed without moving the OR table. In addition, newly developed virtual navigation software (i-guide) can be used in the frameless navigation and access to deep seated intracranial lesions or needle placement. Conclusion: The newly developed robotic DSA system provides safe and precise treatment in the field of endovascular treatment and neurosurgery.